2007
DOI: 10.1021/ja0725706
|View full text |Cite
|
Sign up to set email alerts
|

Tangential Ligand-Induced Strain in Icosahedral Au13

Abstract: A quantitative comparison of first principles calculations with extended X-ray absorption fine structure and transmission electron microscopy measurements provides strong evidence that Au13 nanocrystals are stabilized in a slightly distorted icosahedral structure by on-top phosphine ligands and a combination of on-top and bridging thiol ligands. Importantly, the ligands change the icosahedral strain (i.e., the radial−tangential bond length ratio) significantly, with the tangential bonds within the Au core exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 25 publications
4
57
1
1
Order By: Relevance
“…As we have seen this bond length expansion, also known as compressive strain, is a result of the charge transfer from Au-Au bonds to Au-ligand bonds. At this point, it is worth comparing our results with the findings of Guliamov et al, 23 who also found a compressive strain in icosahedral Au 13 , except that the surface Au-Au bonds were more strongly perturbed than the radial ones, which led them to conclude that a resultant icosahedral geometry should be a distorted one. The difference from our result can be easily attributed to the effect of the S atom in their mixed ligand (PH 3 /SCH 3 ) which adsorbs at the bridge site between two neighboring Au atoms, thereby perturbing the surface Au-Au bond more than the others.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…As we have seen this bond length expansion, also known as compressive strain, is a result of the charge transfer from Au-Au bonds to Au-ligand bonds. At this point, it is worth comparing our results with the findings of Guliamov et al, 23 who also found a compressive strain in icosahedral Au 13 , except that the surface Au-Au bonds were more strongly perturbed than the radial ones, which led them to conclude that a resultant icosahedral geometry should be a distorted one. The difference from our result can be easily attributed to the effect of the S atom in their mixed ligand (PH 3 /SCH 3 ) which adsorbs at the bridge site between two neighboring Au atoms, thereby perturbing the surface Au-Au bond more than the others.…”
Section: Discussionsupporting
confidence: 76%
“…As to adsorption sites, we place the phosphines either on top of Au atoms or in the bridge sites between two neighboring Au atoms, although from the latter position they are always found to move to on-top sites during the energy minimization process used to obtain relaxed structures for the ion cores, in agreement with previous theoretical calculations and experiment. [18][19][20]23 It is noteworthy that we do not see the formation of hydrogen bonds for the phosphine ligands, such as those reported for ligands like ammonia and acetone. 31,32 Figure 2 shows the relaxed geometries of the clusters upon the adsorption of six phosphines.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Kronik et al successfully synthesized Au 13 (PPh 3 ) 4 (SC 12 H 25 ) 4 , and found that the co-protection of thiolates and phosphine ligands leads to the slight distortion of the icosahedral structure. 13 Similarly, Wei and co-workers recently found that the framework of Au 13 (PPh 3 ) 4 (SC 12 H 25 ) 4 is signicantly disturbed by the solvent environment. They found that changing the solvent from ethanol to hexane induces the dissociation of the anionic SR ligands, and the rearrangement of the icosahedral core structure to a face-centred cubic (FCC) structure.…”
mentioning
confidence: 93%